Exploring Relational Understanding in Statistical Problem Solving Based on Secondary School Students’ Learning Styles - Santosa, Yoga Tegar; Nisita, Indriastri; Masduki, Masduki (Universitas Muhammadiyah Mataram, 2025)
Relational understanding is one of the crucial aspects of solving mathematical problems, especially on statistical topics. It enables students to apply procedures correctly and understand the underlying concepts, justify their reasoning, and connect mathematical ideas meaningfully. However, most students still lack relational understanding, reflected in their limited ability to interpret, apply, and connect mathematical concepts meaningfully in problem-solving contexts. Although previous studies have examined relational understanding from various psychological perspectives such as adversity quotient, cognitive styles, and self-esteem no studies have specifically and in-depth explored students' relational understanding based on their learning styles. Therefore, this study aims to explore students' relational understanding skills in solving statistical problems based on their learning styles (visual, auditory, reading, and kinesthetic). This study uses a qualitative approach with a case study design. The participants were 31 seventh-grade students from one of the public secondary schools in Karanganyar Regency, Central Java. Data were collected through learning style questionnaires, mathematical problem-solving tests, and in-depth interviews. Data validity was ensured through triangulation, and the data were analyzed through data reduction, presentation, and conclusion drawing. The results showed that student with a visual learning style fulfilled all indicators of relational understanding, including classifying objects, applying and justifying mathematical procedures, and connecting concepts. Reading-style student also met all indicators, though they showed less strength in defining necessary and sufficient conditions. In contrast, while auditory and kinesthetic learners did not meet all relational understanding indicators, their difficulties varied. Auditory student struggled particularly with justifying procedures and connecting concepts, while kinesthetic learners faced challenges in explaining reasoning and classifying objects. These findings can serve as a reference for teachers and educators in designing instructional strategies that are aligned with students’ learning styles to enhance their conceptual understanding in mathematics.